Tyrosinase inhibitors from fruits of Piper sarmentosum: Isolation, characterization and structure-activity relationship study - Yodsawad, Thita; Meemongkolkiat, Thitipan; Chanchao, Chanpen; Damsud, Thanakorn; Phuwapraisirisan, Preecha (Agriculture and Natural Resources, 2024)
Importance of the work: Piper sarmentosum has long been used in Thai cuisine and traditional medicine. This was the first report on tyrosinase inhibition from the fruits of P. sarmentosum. Objectives: To isolate and characterize the secondary compounds from the fruits of P. sarmentosum together with evaluation of their tyrosinase inhibitory activity. Materials and Methods: The CH2Cl2 and acetone extracts were separated and purified using a variety of chromatographic techniques. The structures of isolated compounds were identified based on their spectroscopic data, particularly nuclear magnetic resonance. The tyrosinase inhibitory activity of the isolated compounds was evaluated using the colorimetric method with kojic acid as the positive control. Results: In total, 21 compounds were isolated from the P. sarmentosum fruits, consisting of 6 phenylpropanoids, 9 phenylpropanamides, 5 alkyl amides and 1 lactone. Compounds 4, 9, and 18 had the most potent tyrosinase inhibitory activity with values for the concentration at 50% inhibition of 1.7 mM, 2.7 mM and 2.8 mM, respectively. Main finding: Phenylpropanoids, phenylpropanamides and alkyl amides showed potent tyrosinase inhibition. This was the first report on tyrosinase inhibition in this plant. Therefore, the fruits of P. sarmentosum have potential for further research for their use in cosmetic and pharmaceutical applications.